Gannet Morus Bassanus ring recoveries suggest shorter migrations than geolocator tracking, but indicate no long-term change in migration distances. Issue 1 (2nd January 2021) - Laurenson, Kirsty; Atkins, Kelly; Clark, Bethany; Morgan, Greg; Morgan, Lisa; Votier, Stephen
ABSTRACT : Capsule: Ring recoveries show no long-term changes in how far south Northern Gannets Morus bassanus migrate or which Large Marine Ecosystem (LME) they were recovered in over nine decades, but underestimate recovery distance compared to geolocation tracking. Aims: To test for change in Gannet migration using ring recoveries from 1930 to 2018 and compare recent recoveries with geolocation tracking. Methods: We analysed latitude and wintering location of 515 ring recoveries of British and Irish Gannets, split by age class, from 1930 to 2018 and compared recent adult tracking and ringing results to test for methodological differences. Results: Adult (age 5+ years) recovery distances were significantly shorter than for immatures (age 2–4) or juveniles (age 1). However, there was no significant temporal trend regardless of age group, either in terms of migration latitude or LME where recoveries were made. By contrast, adult Gannets tracked with geolocators from Grassholm, UK in 2009–2018 had longer migration distances and a higher proportion of birds wintering in the Canary Current Large Marine Ecosystem, compared with ring recoveries over a similar period. Conclusion: Our results highlight discrepancies between ring recoveries and geolocator data, and uncertainty about any potential change in Gannet migration distances.